History‐informed strategy research: The promise of history and historical research methods in advancing strategy scholarship - Argyres, Nicholas S.; De Massis, Alfredo; Foss, Nicolai J.; Frattini, Federico; Jones, Geoffrey; Silverman, Brian S. (Strategic Management Journal, 2020)
Abstract Research Summary The last decade has witnessed an increasing interest in the use of history and historical research methods in strategy research. We discuss how and why history and historical research methods can enrich theoretical explanations of strategy phenomena. In addition, we introduce the notions of “history‐informed strategy research,” distinguishing between the dimensions of “history to theory” and “history in theory” and discussing various under‐utilized methods that may further work on history‐informed strategy research. We then discuss how contemporary research contributes to history‐informed research within the strategy field, examine key methodological and empirical challenges associated with such research, and develop an agenda for future research. Managerial Summary Firms are increasingly making use of their historical past as they reflect on their identities and how these can be used strategically. At the same time, strategy researchers are paying increasing to the use of historical research methods, as well as to how firms use history strategically. We take stock on the role of history in strategy research, outline the key strategic issues that can be informed by a historical way of doing research, discuss the available historical methods, and offer suggestions for future research in the history/strategy intersection.